PROMOTING L2 STUDENTS’ VOCABULARY AWARENESS THROUGH BILINGUAL TEXT IN READING CLASS: A THEORETICAL PERSPECTIVE - Irmayani Irmayani (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2016)
This study presents a literary review on a particular way to promote L2 students’ vocabulary awareness through bilingual text. As it is known, reading class is onne of language skill class which challenge EFL teachers to think and plan more serious to give a good package of teaching and learning in reading class. Poor condition of reading class activity may derive from difficult material for reading activity. This condition leads poor result encouraged more by very low vocabulary mastery. Having mentioned fact, the EFL teacher should have many various material of reading text. Related to reading material, this paper proposes a way to facilitate students’ awareness of vocabulary by providing a bilingual text for reading class. Keywords: bilingual text, vocabulary awareness, reading class